Pengaruh Kepemilikan Pemerintah terhadap Kinerja Perusahaan Badan Usaha Milik Negara yang Terdaftar di BEI - Jessica Angela; Marcelia Jessica; Rinaningsih Rinaningsih; Luciana Haryono (Universitas Prasetiya Mulya, 2020)
This study aims in analyzing the linear relationship between government ownership and company performance in open non-financial State-Owned Enterprises in Indonesia in 2009-2018. The independent variable in this study uses the percentage of government ownership and the dependent variable used are company performance with proxy profitability (Return on Assets, Return on Equity, Return on Sales) and market performance (Tobin’s Q). The independent variable and the dependent variable in the study are supported by two control variables, namely the size of the company and the growth rate of Gross Domestic Product (GDP). The samples used in this study were 152 observation data with panel data to prove the relationship between government ownership and company performance using Stata version 13. The results in the study of the relationship between government ownership and company performance as measured by ROA, ROE, ROS proved to be significantly negative, while Tobin's Q is not related. These results support previous studies, namely Jia et al. (2005), Marciano (2008) in Wiranata and Nugrahanti (2013), Xu and Wang (1999), and Qi, et al. (2000). A significant negative relationship between government ownership and company performance indicates that the government's ability is still not optimal in overseeing the company's operational activities and the objectives of the State-Owned Enterprises focusing on the welfare of a group or the company itself. Keywords: agency conflict, government ownership, company performance, market performance, profitability https://doi.org/10.21632/saki.2.2.203-223